1979
DOI: 10.1152/ajpheart.1979.236.1.h121
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of myocardial contractility to myocardial perfusion

Abstract: Myocardial contractility in open-chest anesthetized (sodium pentobarbital) dogs was varied while ventricular pressure, coronary perfusion pressure, and coronary tone were held constant. Under those conditions, changes in regional blood flow should reflect changes only in intramyocardial compression related to the altered inotropic state. Increasing contractility with isoproterenol caused flow to decrease in the outer myocardial layers without change at the subendocardium. When contractility was decreased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Our finding that contractility is not important in determining the flow impediment in the dog heart, especially for physiological levels of systolic LVP, is consistent with the reports of Klassen & Zborowska-Sluis (1979) and of Trimble & Downey (1979). The former authors, both in the presence and in the absence of autoregulation, reported no alteration in transmural gradient of flow (endo/epi ratio) when the force of contraction of segments of myocardium was increased, while the coronary and ventricular pressure were maintained stable in the physiological range.…”
Section: Implication Of the Findingssupporting
confidence: 92%
“…Our finding that contractility is not important in determining the flow impediment in the dog heart, especially for physiological levels of systolic LVP, is consistent with the reports of Klassen & Zborowska-Sluis (1979) and of Trimble & Downey (1979). The former authors, both in the presence and in the absence of autoregulation, reported no alteration in transmural gradient of flow (endo/epi ratio) when the force of contraction of segments of myocardium was increased, while the coronary and ventricular pressure were maintained stable in the physiological range.…”
Section: Implication Of the Findingssupporting
confidence: 92%
“…Considering the facts that in various animal experimental models other factors, such as perfusion pressure (7), heart rate (9), extravascular compression forces (8,28), vascular remodeling due to medial thickening (2) or perivascular fibrosis (11), and coronary capillary resistance (12), have been implicated in the alterations of maximal myocardial perfusion, their contribution to the difference in the level of maximal perfusion in our two groups of infarcted rats cannot be excluded. However, since our data indicate that perfusion pressure, heart rate, and the size of capillary bed were similar in MI ϩ IVA and MI rats, neither of these factors could affect the level of maximal myocardial perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…First, the increase in heart rate decreases maximum coronary blood flow rates by increasing the total time spent in systole (23). Second, the increased contractility increases systolic compression of the intramural coronary vessels (325,385,533,563). However, the increased contractility simul-taneously augments myocardial relaxation which increases the diastolic perfusion time (142,465,625).…”
Section: Effective Perfusion Pressure: Extravascular Compressive Forcesmentioning
confidence: 99%